Increased Liver Localization of Lipopolysaccharides in Human and Experimental NAFLD. Issue 2 (22nd May 2020) - Carpino, Guido; Del Ben, Maria; Pastori, Daniele; Carnevale, Roberto; Baratta, Francesco; Overi, Diletta; Francis, Heather; Cardinale, Vincenzo; Onori, Paolo; Safarikia, Samira; Cammisotto, Vittoria; Alvaro, Domenico; et al.
Abstract : Background and Aims: Lipopolysaccharides (LPS) is increased in nonalcoholic fatty liver disease (NAFLD), but its relationship with liver inflammation is not defined. Approach and Results: We studied Escherichia coli LPS in patients with biopsy‐proven NAFLD, 25 simple steatosis (nonalcoholic fatty liver) and 25 nonalcoholic steatohepatitis (NASH), and in mice with diet‐induced NASH. NASH patients had higher serum LPS and hepatocytes LPS localization than controls, which was correlated with serum zonulin and phosphorylated nuclear factor‐κB expression. Toll‐like receptor 4 positive (TLR4 + ) macrophages were higher in NASH than simple steatosis or controls and correlated with serum LPS. NASH biopsies showed a higher CD61 + platelets, and most of them were TLR4 + . TLR4 + platelets correlated with serum LPS values. In mice with NASH, LPS serum levels and LPS hepatocyte localization were increased compared with control mice and associated with nuclear factor‐κB activation. Mice on aspirin developed lower fibrosis and extent compared with untreated ones. Treatment with TLR4 inhibitor resulted in lower liver inflammation in mice with NASH. Conclusions: In NAFLD, Escherichia coli LPS may increase liver damage by inducing macrophage and platelet activation through the TLR4 pathway.